ISLAM DI TENGAH ARUS PERKEMBANGAN TEKNOLOGI - Hamzah, Muh (Jurnal Bestari, 1991)
Technology cannot be regarded under its "neutrality" in relation to human life. It is always in close relation with ideology, politic, economy, culture and other aspect of history. It can can be used, both for human welfare and his "bad destiny". It will disturb and destruct their life unless it is held by a true ideology. Islam, as the true "ideology", guides it to the best world. Moslem, therefore, must be able to be the best co pilot for sains andtechnology.